The Relationship Between Lifestyle and the Severity of Diabetic Peripheral Neuropathy at Sapta Medika Indrapura Hospital - Heni Triana; Suherni Suherni; Lilis Pujiati; Chairul Munir (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder whose prevalence continues to increase globally. One of its most detrimental microvascular complications is diabetic peripheral neuropathy (DPN), which is strongly influenced by the patient’s lifestyle. This study aimed to analyze the relationship between lifestyle and the severity of DPN in patients with DM at Sapta Medika Indrapura Hospital. This was a quantitative, descriptive-analytical study with a cross-sectional design. A total of 51 patients with DM were selected through purposive sampling. Lifestyle was measured using the FANTASTIC Lifestyle Checklist (covering family/friends, physical activity, nutrition, smoking, alcohol, sleep/stress, and behavioral patterns), and the severity of DPN was assessed using the Diabetic Neuropathy Score (DNS). Data were analyzed using Spearman’s rho correlation test. Most respondents had an unhealthy lifestyle (68.6%) and experienced severe DPN (64.7%). The Spearman’s rho test showed a significant but weak positive correlation between lifestyle and DPN severity (r = 0.116; p = 0.042; p < 0.05). Lifestyle is significantly associated with the severity of DPN in patients with diabetes, although the association is weak. Healthy behavioral change remains an important strategy to reduce the risk of further complications such as ulceration and amputation. The small, single-center sample limits generalizability, and the cross-sectional design precludes causal inference.Keywords: Diabetes Mellitus, Lifestyle, Diabetic Peripheral Neuropathy, Disease Severity, Indonesia.